2021
DOI: 10.1002/ange.202106259
|View full text |Cite
|
Sign up to set email alerts
|

Der derzeitige Stand von MOF‐ und COF‐Anwendungen

Abstract: Christian Diercks studierte Chemiea nder UniversitätHeidelberg und führte im Grundstudium Forschungsarbeiten in der Gruppe von Prof. Jean-Pierre Sauvage an der Univer-sitätStraßburg sowie an der Northwestern University unter der Leitung von Sir James F. Stoddart durch. Seinen Ph.D. erhielt er 2018 an der UC Berkeley unter der Betreuung von Prof. Omar M. Yaghi fürs eine Arbeit über kovalente organischeG erüstverbindungen. Derzeit ist er Postdoktorandin der Gruppe von Prof. Peter G. Schultz am Scripps Research I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 286 publications
(470 reference statements)
0
29
0
Order By: Relevance
“…Metal-Organic Frameworks (MOFs) are mesoporous hybrid materials self-assembled by metal ions and organic ligands through coordination chemistry. [79] MOFs with porous structures can achieve high drug loading as well as protect proteins from degradation in the gastric environment. [21,80] Tian and co-authors reported an acid-resistant UiO-68-NH 2 constructed MOFs modified with transferrin to overcome the intestinal epithelial barrier for oral insulin (Figure 8a).…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal-Organic Frameworks (MOFs) are mesoporous hybrid materials self-assembled by metal ions and organic ligands through coordination chemistry. [79] MOFs with porous structures can achieve high drug loading as well as protect proteins from degradation in the gastric environment. [21,80] Tian and co-authors reported an acid-resistant UiO-68-NH 2 constructed MOFs modified with transferrin to overcome the intestinal epithelial barrier for oral insulin (Figure 8a).…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…[80b] Apart from MOFs, covalent organic frameworks (COFs), which are composed of organic elements and linked by covalent bonds, also have been applied for drug delivery. [79] Benyettou et al prepared nanoscale COFs as an oral insulin delivery system with a high insulin-loading capacity (65 wt %) due to the high surface area. [82]…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Reticular chemistry has enabled chemists to link discrete molecular building blocks into designed structures such as metal–organic frameworks (MOFs) and covalent organic frameworks (COFs). [ 1–5 ] A target topology is first envisioned, and its nodes are matched by molecular units amenable to being linked together by strong bonds, as illustrated in Scheme . This process, termed augmentation, yields frameworks whose metrics can be precisely tailored by the size of the constituent building units so chosen.…”
Section: A Strategy For Synthesis Of Supercrystalsmentioning
confidence: 99%
“…Concurrently, in the late 1990s, the research on molecular networks evolved toward stabilizing their structures even under vacuum, which provided the creation of permanent porosity in the networks [14,15]. This type of network is called "porous" metal-organic frameworks (MOFs) or "porous" CPs (PCPs), in which metal ions/clusters and anionic organic links are often used as building blocks [16][17][18][19][20]. By following the similar story that the solution chemistry of CCs/MOCs was initiated by cutting out the smallest unit from CPs, the researchers tried to synthesize the molecular counterpart of porous MOFs/PCPs and demonstrated the permanent porosity of CCs/MOCs by gas adsorption experiments in 2005 [21].…”
Section: Introductionmentioning
confidence: 99%